PERLINDUNGAN HAK-HAK PEREMPUAN PASCA PERCERAIAN (STUDI TERHADAP PUTUSAN PENGADILAN AGAMA PALOPO) - Marwing, Anita (PALITA, 2016)
AbstractThis article aims to determine the women rights in Islam, in post-divorce and in knowing theanalysis of judgesâ decision in Palopo Religious Court regarding the women rights afterdivorce. The findings showed that the judges decision regarding the rights of women wereconcluded as follows; 1) the contested or talak divorce cases by verdict judgment did not coverthe wives rights in which judges presumption should not decide the case on the outside of thecharge materials (ultra-petition). So that, the judge did not dare to assign orguarantee the women rights legally after divorcing such as Mutah child custody, property rightsif not being the charge materials. 2) The contested divorce cases did not cover any lawsuitregarding the wives rights. Although the judge had the ex officio rights in determining the wivesrights whether requested or not, the judges of Palopo Religious Court were just in case of thecause of divorce where the husband and wife were not willing to be divorced. So, the judgesutilized their ex officio rights to punish the husbands for providing Mut an according to theirability and feasibility. 3) In reconvenes decision, it was mentioned the wives rights in thejudgesâ decision in which they are Iddah living, Mutah, past living, and the child costs. At theliving Iddah costs, it was decided by Palopo Religious Courts Palopo that it is not in the samenominal amount. It is also similar to the Mutah and children costs.